A study of 4P's in Tabung Haji Travel and Services (THTS) for non muslim perspective - Rahman, Farah Khaliesah (2014)
The purpose of this project paper is to study which 4p's that leads to the number of non muslim perspective in Tabung Haji Travel and Services in Kota Kinabalu Sabah. This research is focusing on the traditional marketing mix which is the for 4p's (Product, Price, Place, and Promotion). The Quantitative data collection method and the random sampling is used to aid the research. Researcher distributed 200 questionnaires and will be analysed by using the SPSS software. The target population for this research is the working peoples and have an interest to go travelling.